Putting down roots: afforestation and bank cohesion of Icelandic rivers ... - Rathburn, Sara; Eysteinsson, Þröstur; Sæmundsson, Þorsteinn; Kemper, John T.; Wieting, Celeste; Friedman, Jonathan M. (Dryad, 2023)
Riparian vegetation is widely recognized as a critical component of functioning fluvial systems. Human pressures on woody vegetation including riparian areas, especially at high latitude, have had lasting effects. In Iceland, prior to human settlement, native downy birch woodlands covered approximately 15–40% of the land area compared to 1–2% today. Afforestation efforts include planting seedlings, protecting native forest remnants, and acquiring land areas as national forests. The planted and protected nature of vegetation along rivers within some forests provides a unique opportunity to evaluate the various taxa within riparian zones and the channel stabilizing characteristics of the vegetation used in afforestation. We investigated bank properties, sediment textures, and root characteristics within riparian zones along four rivers in forests in Iceland. Bank sediment textures are dominantly sandy loam overlying coarser textures. Undercut banks are common because of erosion of the less cohesive subsurface ... : Data were collected at a vertical face of the river bank within a 0.6 m x 0.6 m vegetation grid with 0.1 m x 0.1 m openings. Digital calipers were used to measure roots and classify them into six size categories. ...